Critique of Black Reason - Mbembe, Achille, 1957- (Book collections on Project MUSE., 2017)
Eminent critic Achille Mbembe reevaluates history and racism, offering a capacious genealogy of the category of Blackness-from the Atlantic slave trade to the present-to show how the conjoining of the biological fiction of race with definitions of Blackness have been and continue to be used to uphold oppression.